Combination effect of fluoride dentifrices and varnish on deciduous enamel demineralization - Alessandra Gatti; Lucila Basto Camargo; José Carlos Pettorossi Imparato; Fausto Medeiros Mendes; Daniela Prócida Raggio (Sociedade Brasileira de Pesquisa Odontológica, 2011)
The aim of this study was to evaluate the anticaries potential of 500 or 1100 ppm F dentifrices combined with fluoride varnish using a pH-cycling regimen. Seventy primary canines were covered with nail polish, leaving a 4×4 mm window on their buccal surface, and randomly assigned into 7 groups (n = 10): S: sound enamel not submitted to the pH-cycling regimen or treatment; N: negative control, submitted to the pH-cycling regimen without any treatment; D1 and D2: subjected to the pH-cycling regimen and treated twice daily with 1100 or 500 ppm F dentifrice, respectively; VF: fluoride varnish (subjected to F-varnish before and in the middle of the pH-cycling regimen); and VF+D1 and VF+D2. After 10 days, the teeth were sectioned, and enamel demineralization was assessed by cross-sectional hardness at different distances from the dental surface. Data were analyzed using a two-way ANOVA followed by Tukey's test. Dentifrice with 1100 ppm F and the combination of F-varnish with the dentifrices significantly reduced enamel demineralization compared with the negative control (p < 0.05), but the isolated effects of F-varnish and dentifrice with low concentration were not significant (p > 0.05). The effect of combining F-varnish with the dentifrices was not greater than the effect of the dentifrices alone (p < 0.05). The data suggest that the combination of F-varnish with dentifrices containing 500 and 1100 ppm F is not more effective in reducing demineralization in primary teeth than the isolated effect of dentifrice containing 1100 ppm F.